Outcome after prenatal and postnatal diagnosis of complex congenital heart defects and the influence of genetic anomalies. (4th September 2017) - De Groote, Katya; Vanhie, Ellen; Roets, Ellen; Ramaekers, Paul; De Wilde, Hans; Panzer, Joseph; Vandekerckhove, Kristof; Bove, Thierry; François, Katrien; Van Herck, Koen; De Wolf, Daniël
Abstract: Objective: Determine prenatal detection rate, mortality and association with genetic abnormalities in patients with severe CHD. Method: Single center retrospective study in patients with severe CHD diagnosed prenatally or postnatally (2006 to 2014). Results: A total of 567 patients were included, 176 (31%) after prenatal diagnosis, with large differences in prenatal detection rate among CHD types. Coarctation (24%), tetralogy of Fallot (21%) and univentricular heart (19%) were the most prevalent CHD. Overall mortality rate was 30% with important contributions of prenatal mortality including termination of pregnancy (40%) and postnatal compassionate care (15%). In the group requiring surgery, mortality rate was 12%. Genetic testing was available in 70%. A genetic cause was present in 140/394 patients tested (36%; 25% in the total group). Mortality was higher in the group with abnormal genetic testing compared with those with normal or no genetic testing (57/141 vs 112/423; p  = 0, 002). Conclusion: Only one third of severe CHD are detected; overall mortality remains high (30%) with major contributions of termination of pregnancy and compassionate care. A genetic cause was found in 36% and was associated with a decreased survival. Counseling must include the possibility of associated genetic pathology and its impact on survival. © 2017 John Wiley & Sons, Ltd.